PERANAN KEPOLISIAN DALAM PENERAPAN DIVERSI TERHADAP TINDAK PIDANA YANG DILAKUKAN OLEH ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK OLEH KEPOLISIAN RESOR TAPANULI TENGAH - Erich Sucipto Sinaga; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Children should be protected, including children in conflict with the law. Diversion which means the transfer of the settlement Son of the criminal justice process to the outside of the criminal justice process. Based on the data in the Police Central Tapanuli that recorded 48 cases there are a number of criminal offenses committed by children in 2014 until April 2015 and only one case that getting efforts Diversion. In this case the role of Police Central Tapanuli in the application of Diversi on cases of children in conflict with the law is not maximized. The purpose of this thesis, namely; First, the role of the Police Central Tapanuli in the application of diversion of the offenses committed by children under Act Number 11 of 2012 on the Criminal Justice System Child, Second, Obstacles encountered Police Central Tapanuli in the application of diversion, Third, efforts undertaken Police Central Tapanuli resorts in overcoming barriers to implementation of diversion.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the locations or places studied in order to give a complete and clear picture of the issues examined. This research was conducted at the Police Central Tapanuli, whereas the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, technical data collectors in this study with interviews and literature study.From the research there are three main issues that can be inferred. First, the role of the Police Central Tapanuli in the application of diversion of the offenses committed by children under Act Number 11 of 2012 on the Criminal Justice System Child, that the investigator in charge of the investigation is a special investigator Child/investigator PPA, arrest, detention, examination child in a family atmosphere, the investigator shall ask for consideration/suggestions from Supervising Community, the right to legal assistance in the investigation process and the confidentiality of the child. Second, Obstacles encountered in the implementation of diversion is the capacity in implementing diversion investigators still limited, facilities and infrastructure is not adequate, the lack of cooperation with KPAI. Third, efforts made in overcoming barriers to implementation of diversion, that the training, the process of investigating the diversion in the room for a while. Suggestions Author, First, the police are expected to investigators PPA training and seminars to the public on diversion, Second, the government made in the implementation of the monitoring team of diversion.Keywords : Role of Central Tapanuli Police - Crime of the Child - Diversion